The Use of Vicarious Experience and Enactive Mastery Experience to Improve Career Decision Making in Group Counseling (Jurnal Bimbingan Konseling, 2019)
This study aimed to examine the effectiveness of vicarious experience and enactive mastery experience group counseling to improve the career decision making self-efficacy of the eleventh-grade students of Public Senior High School 1 Bawang Batang. For more, the method used was an experimental research method with randomized pre-test – post-test comparison group experimental design. Also, the results of one way ANOVA showed that group counseling with vicarious experience and enactive mastery experience techniques was more effective to improve career decision making self-efficacy compared to the group counseling which only used one technique. Therefore, this study contributes to considerations in using vicarious experience and enactive mastery experience as interventions to improve Senior High School students’ career decision making self-efficacy.